Impact of Protect-Plus Marketing Program and Customer Health Awareness on purchase intentions for ride-hailing Customers in Indonesia - Valeria Putri Ardanny; Maria Antonieta F Pereira Moniz; Jyotiska Aditya Tjokro; Jeevan Ashok Punjabi; Eddy Yansen (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Covid-19 has impacted businesses on a global scale and ride hailing business in Indonesia is not an exception to the phenomenon, since the Covid-19 had started a lot of government restrictions has been in place in order to combat the spread of Covid-19 in Indonesia. As the restrictions might help to slow the spread of the virus it has also managed to slow the business for ride hailing businesses, such as Gojek in Indonesia as well, due to this phenomenon there has been a lot of push for innovation in Gojek that leads to the creation of Protect+ and other marketing strategy that appeals to Health Awareness. Hence this research is done to find the actual effect of this Protect Plus to the Purchase Intention, specifically to find out whether Protect Plus has a direct or indirect effect to Purchase Intention through Customer Health Awareness and Customer Satisfaction; by conducting a quantitative research through distributing questionnaires to 18-49 age range of Gojek users in Semarang and Jakarta, and through the analysis of the data collected with SmartPLS using a variety of different research measurement methods such as Fornell-Larcker, Cronbach Alpha, P-Value just to name a few; this research concluded that Protect Plus does not have a direct effect on the Purchase Intention but rather an indirect effect to Purchase Intention through Customer Health Awareness and Customer Satisfaction.